The Ghosts Of Rancho Espanto - Cuevas, Adrianna (New York : Farrar Straus Giroux, 2023)
Ages 8-12. Farrar Straus Giroux.
Rafa goes to work on a Rancho Espanto as punishment for a prank gone wrong, where he discovers a mystery as inexplicable as it is familiar and ultimately leads to Rafa learning hard truths about himself.
new kids book 2023 spring.
Grades 4-6.
Keywords: Secrets -- Fiction; Ranches -- Fiction; Friendship -- Fiction; Cuban Americans -- Fiction; Novels